Sorption and bending properties of wood cement panels produced from mixed Nigerian hardwoods at varying water/cement ratios (2013)
The study was carried out to investigate the influence of water/cement ratio on the moisture response and mechanical properties of wood cement panels fabricated with mixed hardwood species. The experimental boards so produced were subjected to modulus of rupture (MOR), modulus of elasticity (MOE), water absorption (WA), thickness swelling (TS) and linear expansion (LE) tests. Data collected were subjected to statistical analysis using ANOVA and multiple linear regressions MOR and MOE ranged from 4.94 N/mm2 to 11.63 N/mm2 and 2340 N/mm2 to 4880 N/mm2 respectively. Strength (MOR) and stiffness (MOE) of the boards increased as water/cement ratio was raised from 0.50 to 0.60. With these ranges, more dimensionally stable cement-bonded particleboards were obtained. As water/cement ratio was however raked from 0.60 to 0.65, weaker and inferior boards were produced. The results of the multiple regression analysis showed that water/cement ratio (WCR), cement/wood mixing ratio (MR) and board density (BD) were positively correlated with MOR and MOE. Water absorption (WA), thickness swelling (TS) tests ranged from 16.27 to 48.82% and 0.49 to 2.30% respectively, Statistical analysis of the results showed that the process variables WCR, BD and MR were significant at 1% level of probability on WA and TS. Moiture uptake and swelling of .the panel decreased as water/cement ratio was raised from 0.50 to 0.60. Inferior panels were produced when water/cement ratio was increase beyond 0.60. Therefore 0.60 was considered uptimum level for board fabrication in this study.